Mathematical Modeling of Blood Flow Through a Stenosed Bifurcated Artery With Heat Source and Magnetic Effect - Rao, G. Madhava; Srinivasacharya, D.; Suman, G. Venkata (Communications in Mathematics and Applications, 2021)
The present article illustrates the influence of heat source on MHD blood flow in a branched artery with small obstacle in its main artery by treating blood as micropolar fluid. Artery forming branch is presumed as straight cylinder of restricted length and is symmetric about its axis. The irregular shape of constricted branched artery is changed to a well defined shape by utilizing a  adial coordinate transformations. Numerical solution is computed for interested physical quantities such as rate of flow, and shearing stress on one as well as the other sides of the apex.
Keywords: Blood flow; Micropolar fluid; Branched artery; Mild constriction; MHD; Heat source